Hubungan Kinerja Perawat Dengan Kepuasan Pasien Di Ruang Rawat Inap Rumah Sakit Tk. III 04.06.03 Dr. Soetarto Yogyakarta - Agus Sarwo Prayogi (Universitas Muhammadiyah Tangerang, 2018)
The good performance of nurse is a guarantee of quality of health care provided to patients either sick or healthy. Through the performance of nurses is expected to show real professional contribution in improving the quality of nursing service, the impact on health services, and the eventual impact on quality of life and welfare of the community. Nurses' performance is measured from the services provided to the patient so that the patient feel satisfied or dissatisfied. patient dissatisfaction arises because the gap between the expectations of patients with the performance of the service he felt while using health services. If the level of patient satisfaction is not fulfilled, then the obstacles often faced by health services is a complaint. If the performance is below expectations, then the customer will be disappointed. When performance suitable with expectations, then the customer will be very satisfied. Patient satisfaction has correlated with the performance of nurses who provide care to the patient. To know the correlation between the performance of nurses with patient satisfaction in inpatient. This study was done with quantitative methods (non-experimental) with descriptive correlation research type. With cross sectional approach. The number of sample in this study were 71 respondents by using purposive sampling techniques, data analysis by using the Correlation Kendall Tau. The results showed that the performance of nurses in inpatient room of TK III 04.06.03 Dr. Soetarto hospital is enough (40.8%), Patient satisfaction in inpatient room of TK III 04.06.03 Dr. Soetarto hospital is sufficient satisfaction (39.4%). There is a significant correlation between the performance of nurses with patient satisfaction, with a correlation coefficient of 0.646 with a p-value of 0.000 (p <0.05), means there is the good performance of nurses will increase patient satisfaction. Conclusion: There is correlation of nurses performance with patient satisfaction in inpatient room. Keywords: Nurse Performance, Patient Satisfactions